2016
DOI: 10.3847/0004-637x/832/1/58
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Monitoring of the Coldest Known Brown Dwarf With the Spitzer Space Telescope*

Abstract: Because WISE J085510.83−071442.5 (hereafter WISE 0855-0714) is the coldest known brown dwarf (∼ 250 K) and one of the Sun's closest neighbors (2.2 pc), it offers a unique opportunity for studying a planet-like atmosphere in an unexplored regime of temperature. To detect and characterize inhomogeneities in its atmosphere (e.g., patchy clouds, hot spots), we have performed time-series photometric monitoring of WISE 0855-0714 at 3.6 and 4.5 µm with the Spitzer Space Telescope during two 23 hr periods that were se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…In contrast, were unable to conclusively constrain the presence of clouds or non-equilibrium chemistry in its atmosphere when comparing photometry in six optical and near-IR bands to model predictions. Finally, Esplin et al (2016) reported variability at 3.6 μm and 4.5 μm with peak-to-peak amplitudes between 3-5 per cent and also found insufficient evidence for water ice clouds in the atmosphere. Periodicity in the observed variability was inconclusive, with periods ranging between 6.8-9.0 h at 3.6 μm and 5.3-9.3 h at 4.5 μm for two different epochs.…”
Section: Ta R G E T Smentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast, were unable to conclusively constrain the presence of clouds or non-equilibrium chemistry in its atmosphere when comparing photometry in six optical and near-IR bands to model predictions. Finally, Esplin et al (2016) reported variability at 3.6 μm and 4.5 μm with peak-to-peak amplitudes between 3-5 per cent and also found insufficient evidence for water ice clouds in the atmosphere. Periodicity in the observed variability was inconclusive, with periods ranging between 6.8-9.0 h at 3.6 μm and 5.3-9.3 h at 4.5 μm for two different epochs.…”
Section: Ta R G E T Smentioning
confidence: 90%
“…WISE 1405+55 was discovered and initially classified as a Y0p? dwarf by Cushing et al (2011), Esplin et al (2016) report the listed Lomb-Scargle periodogram peaks for 3.6 μm or 4.5 μm, respectively, for two different epochs. They also report that a double sinusoid model in which one period is twice that of the other returns 9.7 +0.9 −0.8 /10.8 +0.7 −0.7 for 3.6 μm or 4.5 μm, respectively, the first epoch and 14 +2 −2 /13.3 +0.5 −0.4 for the second epoch.…”
Section: Ta R G E T Smentioning
confidence: 97%
See 2 more Smart Citations
“…However, Skemer et al (2016) and Morley et al (2018) disputed the Luhman & Esplin (2014) result and validated water ice clouds as the interpretation for the absorption features in the 3.4-5.2 μm spectra. Finally, photometric variability at a 4% level was detected in WISEJ0855−0714 in the mid-infrared (Esplin et al 2016), suggesting a patchy atmosphere, yet the cloud composition remains unclear. WISEAJ0830+2837, along with CWISEPJ1935−1546 and CWISEP1446−2317, fill an important gap in the Y-dwarf sequence to continuously map atmospheric composition across low temperatures down to Jupiter.…”
Section: Characterization Of Low-temperature Atmospheres From the T/mentioning
confidence: 96%